An experimental and field study of cavitation detection in pump - Tan, Chek Zin (2007)
Cavitation represents one of the most common faults in pumps and could potentially lead to a series of failures in mechanical seal, impeller, bearing, shaft, motor, etc. In this work, an experimental rig was setup to investigate cavitation detection using vibration analysis method, and measured parameters including sound, pressure and flow rate for feasibility of cavitation detection. The experimental testing includes 3 operating points of the centrifugal pump (Best Efficiency Point, 90% of Best Efficiency Point and 80% of Best Efficiency Point). It was shown that the high frequencies random vibration in the fast fourier transform (FFT) spectrum was vital and applicable for cavitation diagnosis. Cavitation was found to have easily excited natural frequencies of the pump components. There was a significant vibration amplitude increase at the frequency of Â½ of blade passing frequency (BPF) in the envelope spectrum during cavitation existence. High impulsive spikes were clearly evident in the vibration time signal of cavitation. A grinding sound synonymous with cavitation was clearly audible during cavitation. Margin ratio of net positive suction head (NPSH), suction energy, cavitation number and flow rate were proven to be a good indicator for detecting cavitation. The findings of the experimental results were consistent for all test conditions. The field investigation of two submerged vertical pumps with suspected cavitation and flow induced vibrations in a power plant are presented. Such pumps do not have an adequate pressure and flow instrumentation that could detect abnormal hydraulic operating conditions. These pumps had a history of catastrophic impeller failures and the failure modes showed cavitation erosion and a sheared impeller blade. High frequencies random vibration was a good indicator for flow excitation and cavitation in the field investigation. Evidence of an excessive clearance and/or sleeve bearing wear were also noted in the pump of concern. The field investigations confirmed concern relating to operations during low tide and combined pumps operated in parallel where inadequate submergence were identified as the likely causes to the impeller failures. The impeller of concern was identified as not being the root cause of the problem. The investigations implied a system design problem and pump operating conditions compounding the system design error that had resulted in frequent failures of the pumps.